Developing a Deep Learning-Based Legal Literacy Education Model: Structural Relationships Among Digital Legal Literacy, Cyber Behavior, Learning Needs, and Character Strengthening - Radini; Otang Kurniaman; Zufriady; Mifta Rizka; Beny Al Fajar; Ningrum Melihayatri; Viony Syafitra (Jurnal PAJAR (Pendidikan dan Pengajaran), 2026)
The rapid growth of digital technology has created new challenges related to legal awareness, ethical behavior, and character development among students. As digital natives, students are increasingly exposed to various online activities that require not only digital literacy but also an understanding of legal rights, responsibilities, and ethical principles. This study aims to develop and validate a Deep Learning-Based Legal Literacy Education Model by examining the structural relationships among Digital Legal Literacy, Cyber Behavior, Learning Needs, and Character Strengthening. A quantitative research approach employing a survey design was adopted. Data were collected from 100 elementary school students through a structured questionnaire consisting of 25 indicators representing five latent constructs. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The results indicate that the measurement model demonstrates satisfactory validity and reliability. The structural model confirms that Digital Legal Literacy significantly influences Cyber Behavior, Learning Needs, and the Deep Learning-Based Legal Literacy Education Model. Furthermore, Learning Needs play a crucial role in shaping the educational model, while the Deep Learning-Based Legal Literacy Education Model emerges as the strongest predictor of Character Strengthening. The findings highlight the importance of integrating legal literacy, digital citizenship, and deep learning pedagogies to foster responsible digital behavior and positive character development. This study contributes to the advancement of educational theory by providing an empirically validated framework that integrates legal literacy education, deep learning, and character education. The proposed model offers practical implications for educators and policymakers seeking to prepare students as ethical, responsible, and legally aware digital citizens in the digital era.